30 Rock. Season 5 [videorecording (DVD)] - Fey, Tina, 1970- (Universal Studios Home Entertainment, 2011)
In this behind-the-scenes romp about sketch show TGS, corporate executive Jack Donaghy, TGS neurotic stars, a hapless NBC page, and the rest of the befuddled crew work to create the 'magic of television.' Brought to you by the folks at GE Kabletown, it's a season of video obituaries, cross-dressing love, page showdowns, Canadian births, and other strange events in 22 blerg-worthy episodes.